Pengaruh Kualitas Layanan dan Promosi Terhadap Keputusan Donatur Membayar ZIS di Surabaya - Satria, Naufal Prima; Ajib Ridlwan, Ahmad (Jurnal Ekonomika dan Bisnis Islam, 2019)
This study aimed to examine the effect of the Islamic services quality and Islamic promotion on the decision of donors to pay zakah, infaq, and alms funds at the amil zakah institution in the city of Surabaya. This study used associative quantitative methods. The number of samples used in this study were 115 respondents. This study used a Likert scale and analyzes it using the SPSS application. The results of this study indicated the Islamic services quality and Islamic promotion have a positive effect on donor decisions. Furthermore, this study showed on the results of the partial test, the Islamic services quality influences donor decisions and the Islamic promotion influence donor decisions.